Indications of the Implementation in the Process of Educational Reform in Uruguay - Sarasola, Marcos R. (Education Policy Analysis Archives, 2000)
In this paper the author investigates, from a qualitative perspective, the problems associated with implementing educational innovations. He studies the recent case of the Basic Cycle reform in Uruguay. Based on the concepts of van der Vegt and Vandenberghe (1992), he analyzes the "functions guides" exercised by the director in order to be able to regulate the internal flow of the implementation. The first of these is "conceptual clarity", which has to do with providing the professors with a clear vision of what will take place within the implementation, and with specifying that vision in terms of the professional knowledge and abilities of the faculty as well. The second of these is "directional pressure," which refers to an operational level of the implementation; that is to say, how daily activities mesh with the objectives of the reform. Next, "function of support" refers to the support offered by the director for the management of resources (material, emotional, technical, and administrative resources), so that the resources may then effectively support the work in the center. Finally is "definition of latitude," that is, the degree of educational autonomy that the faculty have with respect to the external objectives of the reform.